Dementia as a Risk Factor for Bullous Pemphigoid: Síndrome Demencial como Fator de Risco para Penfigoide Bolhoso - Graça, Carina; Pacheco, Márcia; Moitinho, Marta; Macias, Vasco; Dessai, Sunita; Barata, José (Gazeta Médica, 2017)
Bullous pemphigoid is an acquired autoimmune skin disease, more often in the elderly. Recent studies have shown the association between bullous pemphigoid and neurological diseases. We present the case of an 80-year-old female, with prior history of Parkinson’s disease, admitted in our ward with an extensive bullous dermatosis involving the trunk, upper limbs and thighs, consisting of erythematous vesicular lesions, with no involvement of the mucosae. After the confirmation by the skin biopsy, positive direct immunofluorescence and exclusion of other causes, the diagnosis of bullous pemphigoid was established. She was submitted to targeted treatment with prednisolone, azathioprine and doxycycline, with favorable clinical evolution. This clinical case highlights the importance of early diagnosis in patients with demential diseases. The delay in treatment of this autoimmune skin can lead to serious complications.